METHOD OF TREATMENT OF CONSTITUTIONAL PUBERTY RETARDATION IN BOYS (CASE HISTORY) - A. A. Sinitsina; N. V. Bolotova; S. М. Sharkov; Yu. M. Raigorodskii; O. M. Konnova ("Paediatrician" Publishers LLC, 2012)
The results of examination of a 15-year-old boy with growth and puberty retardation are analyzed in this article. On the grounds of performed complex examination the patient was found physical development delay, changes at the endocrinal status, as well as pathological signs on X-ray, rheo- and electroencephalography, which are characteristic for functional growth and puberty retardation. In order to correct the found disturbances transcranial magnetotherapy was carried out. During the performed treatment improvement of the physical development characteristics, endocrinal status and data of rheo- and electroencephalography were noted.